Od ekologii i neo-ekologii człowieka do sozoekologii społecznej - Wierzbicki, Zbigniew (Wydział Prawa i Administracji UAM, 1986)
The author departs from the assumption that there is no clear cut borderline between a human constitution and a natural environment, as these two consist the interrelated system, interacting in the respect of conditioning. Analysing the state of natural environment in Poland, the author is searching for the explication of the ecological crisis not only in the sphere of industrialization and urbanization processes in the country and applying no protective installations, but he is also offering reasons for it, of a social nature: the lack of tripartite division of powers (according to the Montesqueiean theory), and the lack of equilibrium of social powers which is practically manifested by the domination of a techno-bureaucratic lobby over other socio-professional structures as well the supremacy of the planning and executive power over the other ones. The traditional ecology and neo-ecology of a man are not relevant to the existing situation. New ideas and concepts have appeared (ecoarchitecture, eco- -pedagogics, eco-economics), as well as the desire, and sometimes the necessity to shape the environment directly (sociospatial planning) with the respect to problems of natural environment protection (sozo-ecology, or sozo-physiotactics; a Gr. word „sozo-" protect, keep alive) to save a man and his civilization. It is the author's suggestion to supplement the ecology of man by introducing a planning to the cultural order, to prevent degrading of nature by means of regulating economic competition in the biotic order (on a local level). Activity of man aiding the nature would be an ideal solution, or at least the activity not destructing it. The author precises the differences between the old ecology and new-ecology of man and social sozo-ecology, mentioning the following in the new concept: a wider understanding of the natural environment (also woods, waters wasteland, and monuments of the material culture independently of their economic use); space has a „continous" value irrespective of its economic use, evaluating it according to sozo-ecological or (sociological criteria (as an element of the non-spatial system of values- F. Znaniecki); particular importance is attributed here to rural and protected areas (e.g. national parks, wasteland) as to the „supplier" of ecological resources to the areas exhibiting their deficit, and as a condition of the ecological balance of a region or country. A notion of „subsocial relations" is reintroduced in sozo-ecology, to define solely interactions between men and nature.
From ecology and neo-ecology of a man to social-sozoecology